1996
DOI: 10.2337/diab.45.5.659
|View full text |Cite|
|
Sign up to set email alerts
|

Oral Vanadyl Sulfate Improves Insulin Sensitivity in NIDDM but Not in Obese Nondiabetic Subjects

Abstract: We compared the effects of oral vanadyl sulfate (100 mg/day) in moderately obese NIDDM and nondiabetic subjects. Three-hour euglycemic-hyperinsulinemic (insulin infusion 30 mU / m / min) clamps were performed after 2 weeks of placebo and 3 weeks of vanadyl sulfate treatment in six nondiabetic control subjects (age 37 +/- 3 years; BMI 29.5 +/- 2.4 kg/m2 ) and seven NIDDM subjects (age 53 +/- 2 years; BMI 28.7 +/-1.8 kg/m2). Glucose turnover ([3-3 H]glucose), glycolysis from plasma glucose, glycogen synthesis, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
54
1
2

Year Published

1999
1999
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(58 citation statements)
references
References 0 publications
1
54
1
2
Order By: Relevance
“…In people with diabetes and overt hyperglycemia, oral administration of vanadium compounds did result in modest improvement in glucose concentrations (38,39). However, when administered to subjects with insulin resistance who did not manifest hyperglycemia, vanadate had no significant effect (40). These clinical observations are consistent with a more potent effect of vanadium in the presence of elevated glucose.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…In people with diabetes and overt hyperglycemia, oral administration of vanadium compounds did result in modest improvement in glucose concentrations (38,39). However, when administered to subjects with insulin resistance who did not manifest hyperglycemia, vanadate had no significant effect (40). These clinical observations are consistent with a more potent effect of vanadium in the presence of elevated glucose.…”
Section: Discussionsupporting
confidence: 77%
“…Oral administration of vanadate and vandyl resulted in lowering of glucose concentrations in rodent models of both type 1 and type 2 diabetes (34 -37). Recent studies in human diabetic subjects suggest that these vanadium compounds can lower glycemia and improve lipid levels (38,39), whereas this treatment was less effective in improving insulin resistance in nondiabetic obese subjects (40). The mechanism by which vanadate mimics insulin is not completely clear.…”
mentioning
confidence: 99%
“…8 The increasing interest is mainly owing to the role of vanadium in several biological processes such as the regulation of glucose level in the blood of diabetic animals and patients. 3,4,[9][10][11][12][13][14][15][16][17] Moreover, decavanadate and oxovanadates have many biological activities and been successfully used for the comprehension of several biochemical processes. 18 Other interest for vanadium oxides is sourced from their potential uses as secondary cathode materials, both catalysis and electronics.…”
Section: Introductionmentioning
confidence: 99%
“…Vanadium acts as phosphate analog and exerts effects on several steps in the insulin signaling pathways [45]. Animal model studies showed that vanadium enhanced insulin sensitivity and increased glucose uptake [47,48].…”
Section: Discussionmentioning
confidence: 99%